Molecular epidemiology of carbapenem-resistant Acinetobacter baumannii from Southern Brazil - de Paula Gollino, Gabriel (2021)
Carbapenem resistance in Acinetobacter baumannii has reached extremely high levels worldwide and class D OXA-type carbapenemases are the main associated mechanism. The aim of this study was to evaluate the phenotypic and molecular profile of clinical carbapenem-resistant A. baumannii (CRAb) isolates from a southern Brazilian border region. A. baumannii species was identified by the presence of the blaOXA-51 gene and the susceptibility profile was determined by broth microdilution. The main carbapenemases were investigated by PCR and the typing of the CRAb isolates was performed by PFGE. During the study period, a total of 36 CRAb were recovered, 71.4% from respiratory tract samples from ICU patients. High level resistance to aminoglycosides and fluroquinolones were found in contrast to polymyxin B, for which all of CRAb were susceptible. The blaOXA-23 gene was present in 34 isolates and was the only one detected other than blaOXA-51. Molecular typing revealed the presence of four clonal strains, two of them endemic throughout the study period. To the best of our knowledge, our study brings the first data about resistance profile in Acinetobacter in the western border of south of Brazil and make aware of endemic clones of CRAb-producing-OXA-23 in this region of state, contributing for the construction of the national epidemiologic scenario of CRAb.